After sudden unexpected death in epilepsy: Lessons learned and the road forward. (January 2016) - Donner, Elizabeth J.; Waddell, Briony; Osland, Karen; Leach, John P.; Duncan, Susan; Nashef, Lina; Picot, Marie Christine
Summary: The devastating effects of sudden unexpected death in epilepsy (SUDEP) can be difficult to navigate, even for experienced clinicians. Mounting evidence supports full disclosure of the risks of epilepsy to those affected and their caregivers, and recommendations from regulatory and professional groups encourage the same. Following a death, families are faced with tragedy, guilt, and sometimes anger. Clinicians are often called upon to provide information and support. The development of a comprehensive approach to SUDEP education requires careful consideration of the people living with epilepsy, facts about SUDEP and known risk factors, as well as experiences of families and care providers. In this article, we share the experiences of those working in SUDEP education and epilepsy care, including the voluntary sector. We explore the experience of bereaved families and clinicians, derive lessons from published research, highlight areas where more research is needed, and report on preliminary data from a nationwide study from France.